Interactions among cereal cyst nematode Heterodera filipjevi, dryland crown rot Fusarium culmorum, and drought on grain yield components and disease severity in bread wheat. Issue 3 (4th May 2022) - Ahmadi, Mahin; Mirakhorli, Neda; Erginbas-Orakci, Gul; Ansari, Omid; Braun, Hans-Joachim; Paulitz, Timothy; Dababat, Abdelfattah A.
Abstract: The cereal cyst nematode (CCN) Heterodera and crown rot caused by Fusarium species limit cereal production and yield potential. Losses increase when CCN and crown rot occur together, especially under water stress conditions. The objective of this study was to investigate the interactions among Heterodera filipjevi, Fusarium culmorum, and drought on a set of wheat germplasm with differing levels of resistance/tolerance to CCN, crown rot and drought. Plant emergence was significantly reduced (56% seedling death) when seeds were planted in a water stress environment where F. culmorum and H. filipjevi were present. Crown rot was more severe under water stress compared with Fusarium inoculation alone. The number of cysts fell significantly when H. filipjevi was co-inoculated with F. culmorum, revealing an antagonistic interaction between the nematode and fungus. The highest number of cysts was found on the susceptible accession 'Seri' under water stress conditions. Water stress caused a significant reduction in plant height, while F. culmorum inoculation did not, unless combined with water stress. Yield components were significantly reduced by each of the single stresses and losses were greater when plants were exposed to double or triple stresses. Water stress and F. culmorum inoculation caused a significant reduction in spike weight and seeds per spike. The chlorophyll content of wheat leaves was negatively affected by water stress and inoculation by both nematode and fungus. In conclusion, water stress exacerbates the damage caused by CCN and crown rot, and planting drought-resistant varieties would be an ideal solution to reduce losses.